2019
DOI: 10.1007/s12520-019-00873-w
|View full text |Cite
|
Sign up to set email alerts
|

Late production of Egyptian blue: synthesis from brass and its characteristics

Abstract: This work follows the recent discovery of a zinc-bearing Egyptian Blue (EB) pigment widely used for the production of the early medieval mural paintings cycle in Santa Maria foris portas church at Castelseprio (Lombardy Region, Italy).The inclusion of zinc in the synthesis of EB has been studied for the first time trying to evaluate whether its addition could be casual or deliberate. Historical reconstructions of the pigment have been carried out with a special focus on the use of zinc besides copper, using di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 47 publications
(35 reference statements)
0
30
0
Order By: Relevance
“…Based on elemental analysis, arsenical copper alloys have been identified as the copper source for Egyptian blue production in the Old Kingdom, which was replaced by bronze scrap from the second half of the second millennium BCE and until the Roman period [1,41,50]. Later Egyptian blue productions indicate the use of brass (copper-zinc alloy) for the production of Egyptian blue [69]. These observations suggest a preference for the use of copper alloys instead of metallic copper or copper ores for the production of Egyptian blue.…”
Section: Resultsmentioning
confidence: 99%
“…Based on elemental analysis, arsenical copper alloys have been identified as the copper source for Egyptian blue production in the Old Kingdom, which was replaced by bronze scrap from the second half of the second millennium BCE and until the Roman period [1,41,50]. Later Egyptian blue productions indicate the use of brass (copper-zinc alloy) for the production of Egyptian blue [69]. These observations suggest a preference for the use of copper alloys instead of metallic copper or copper ores for the production of Egyptian blue.…”
Section: Resultsmentioning
confidence: 99%
“…the well-known Bust of Queen Nefertiti). [49][50][51][52][53] HB and HP, on the other side, were mostly employed in the times of the Qin and Han dynasties (≈220 BC-220 AD), as witnessed by e.g. the Terracotta Warriors of the tomb of Emperor Qin Shihuangdi in Xi'an.…”
Section: Sebastian Krussmentioning
confidence: 99%
“…Previous works have demonstrated that silanol groups are indeed accessible in significantly high numbers as a consequence of both synthesis and exfoliation procedures 22,35,73 . Our goal was to first demonstrate that this chemistry works in general and then to use it to bind biologically relevant molecules to EB-NS.…”
Section: Functionalization (Ebfunc) Of Egyptian Blue Nanosheets (Eb-n...mentioning
confidence: 99%